Granulocyte Colony-Stimulating Factor Accelerates the Recovery of Hepatitis B Virus-Related Acute-on-Chronic Liver Failure by Promoting M2-Like Transition of Monocytes - Tong, Jingjing; Wang, Hongmin; Xu, Xiang; Wan, Zhihong; Fang, Hongbin; Chen, Jing; Mu, Xiuying; Liu, Zifeng; Chen, Jing; Su, Haibin; Liu, Xiaoyan; Li, Chen; et al. (Frontiers in Immunology, 2022)
Background and Aim Acute-on-chronic liver failure (ACLF) has a high mortality rate. The role of granulocyte colony-stimulating factor (G-CSF) in ACLF remains controversial. Monocytes/macrophages are core immune cells, which are involved in the initiation and progression of liver failure; however, the effect of G-CSF on monocytes/macrophages is unclear. The study aimed to verify the clinical efficacy of G-CSF and explore the effect of it on monocytes in hepatitis B virus (HBV)-related ACLF (HBV-ACLF) paitents. Methods We performed a large randomized controlled clinical trial for the treatment of HBV-ACLF using G-CSF. A total of 111 patients with HBV-ACLF were prospectively randomized into the G-CSF group (5 μg/kg G-CSF every day for 6 days, then every other day until day 18) or the control group (standard therapy). All participants were followed up for at least 180 days. The relationship between monocyte count and mortality risk was analyzed. The effect of G-CSF on the phenotype and function of monocytes from patients with HBV-ACLF was evaluated using flow cytometry in vivo and in vitro experiments. Results The survival probability of the G-CSF group at 180 days was higher than that of the control group (72.2% vs. 53.8%, P = 0.0142). In the G-CSF-treated group, the monocyte counts on days 0 and 7 were independently associated with an evaluated mortality risk in the fully adjusted model (Model 3) [at day 0: hazard ratio (HR) 95% confidence interval (CI): 15.48 (3.60, 66.66), P = 0.0002; at day 7: HR (95% CI): 1.10 (0.50, 2.43), P=0.8080]. Further analysis showed that after treatment with G-CSF in HBV-ACLF patients, the expression of M1-like markers (HLA-DR and CD86) in monocytes decreased (HLA-DR: P = 0.0148; CD86: P = 0.0764). The expression of MerTK (M2-like marker) increased (P = 0.0002). The secretion of TNF-α, IL-6, and IL-10 from monocytes decreased without lipopolysaccharide (LPS) stimulation (TNF-α: P < 0.0001; IL-6: P= 0.0025; IL-10: P = 0.0004) or with LPS stimulation (TNF-α: P = 0.0439; P = 0.0611; IL-10: P = 0.0099). Similar effects were observed in vitro experiments. Conclusion G-CSF therapy confers a survival benefit to patients with HBV-ACLF. G-CSF can promote the anti-inflammatory/pro-restorative phenotype (M2-like) transition of monocytes, which may contribute to the recovery of ACLF. Clinical Trial Registration Number ClinicalTrials.gov, identifier (NCT02331745).